A simple recipe for rapid all-optical formation of spinor Bose–Einstein condensates. (10th July 2017) - Huang, Chih-Yuan; Chen, Chun-Chia; Sun, Li-An; Liao, Guan-Bo; Wu, Keng-Shuo; Lin, Yu-Ju; Chang, Ming-Shien
Abstract: We present a simple recipe for the rapid formation of spinor Bose–Einstein condensates of 87 Rb atoms in a three-beam crossed optical dipole trap (ODT). Two laser Gaussian beams were crossed at a small angle to form an effective single potential in the intersection region with an independent and widely tunable trap volume and aspect ratio, for both efficient atom loading and number density enhancement. A third Gaussian beam was then introduced to create a potential dimple at the trap center to further increase the atom number density and collision rate, which enabled rapid evaporation to a Bose condensation. In this configuration, 2 × 10 6 atoms were loaded into the three-beam crossed trap from a vapor cell magneto-optical trap, and condensates of 3 × 10 4 – 4.5 × 10 4 atoms were created after 3–5 s of rapid evaporation. The demonstration of efficient and robust BEC production in this ODT suggests the applicability of this trapping geometry to lasers with any far off-resonant wavelengths. To prepare the spinor condensates with a wide tunability of spin population, control of the magnetic fields was first employed during evaporation to polarize the spin states, and the tuning mechanism is discussed. Spinor condensates with an arbitrary spin population were then created via multiple microwave pulses driving the ground hyperfine transitions.